HUBUNGAN FORWARD HEAD POSTURE DENGAN KESEIMBANGAN STATIS PADA SISWA SMAN 1 SEMARAPURA - Dewa Ayu Puspitasari; Ari Wibawa; I Dewa Ayu Inten Dwi Primayanti (Majalah Ilmiah Fisioterapi Indonesia, 2018)
ABSTRACT Forward head posture is a posture problem which experienced by most school-age students. Forward headposture results in disproportion of postural muscles function. The aim of the study was to investigate the correlationbetween forward head posture with static balance control in which implemented a cross-sectional analytic design. Thepopulation of this study was students in age of 15-18 years old at SMAN 1 Semarapura. The participants were 84students selected by using purposive sampling technique. Data were taken by Forward Head Test and One Leg StanceTest. The data of the test were analyzed by Spearman’s Rho Test with significance value p<0.05. The result showedthat the best static balance control category mostly owned by normal head posture group (7 students). On the otherhand, below average static balance control category mostly owned by forward head posture group (18 students). It wasalso founded the p value from the Spearman’s Rho Test was 0.004 (p<0.05) and the correlation coefficient value was 0,310. The conclusion there is a correlation between forward head posture with static balance control of students inSMAN 1 Semarapura. Keywords: forward head posture, static balance control